El proyecto EPICC: Mejora de la competencia de enfermeras y parteras en atención espiritual a través de educación innovadora y atención compasiva (Paraninfo Digital, 2024)
The EPICC project was conducted between November 2016 and July 2019. It generated a rich insight into current educational practice across Europe and provided an opportunity for the sharing of best practice. A significant output from the project was the development of a more uniform approach to how personal, religious and spiritual beliefs can be incorporated into nursing and midwifery programmes. It was felt by adopting this more uniform and integrated approach to the teaching of these concepts it may enable practitioners to meet the unmet spiritual needs of patients. Utilisation of the outputs and toolkit from the study provide a means for informing and aiding the adoption of enhanced spiritual care education. The provision of the toolkit facilitates spiritual care nursing/midwifery education throughout Europe and beyond. The Matrix for spiritual care education enables standardized teaching and learning for undergraduate nursing and midwifery students across diverse cultural and social groups focused on measurable and replicable competences, which can be utilized globally in nursing and midwifery education.